MINDFULNESS IN TOUCH THERAPY: A SYSTEMATIC LITERATURE REVIEW - Fendy, Fendy; Utomo, Budi; Suherman (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study presents a literature review of mindfulness in touch therapy, based on the definition of mindfulness, the key terms that accompany it, and the practices involved. The literature review reveals the proven role of mindfulness in helping to reduce psychological distress inherent in illness condition. This study uses the System Literature Review (SLR) method to analyze previous relevant research on mindfulness in touch therapy. Meta-synthesis was consducted to answer the research question, namely how is the practice of mindfulness in the field of touch therapy practice. The purpose of this SLR study is to gain a deeper understanding of mindfulness in touch therapy; improve understanding through a literature study of five selected studies; thoroughly examine the research and intensity of discussion; and provide evidence that the application of mindfulness is effective in supporting the process of touch therapy.